Evaluation of glucocorticoid in treatment for patients with acute respiratory distress syndrome - Song, Zhi-fang (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2003)
OBJECTIVE: To value of glucocorticoid (GC) in treatment for patients with acute respiratory distress syndrome (ARDS) was evaluated